2011
DOI: 10.1161/atvbaha.111.228304
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Alpha 1-Induced RhoA Phosphorylation Mediates Vasoprotective Effect of Estradiol

Abstract: Objective-Estradiol (E2) mediates numerous beneficial effects assigned to estrogens, but whereas mechanisms have been described at the endothelial level, direct effects on vascular smooth muscle cells (VSMC) are poorly documented. As evidence accumulates regarding the role of RhoA in vascular pathophysiology and the benefit of RhoA-Rho associated protein kinase (Rock) pathway inhibition, we analyzed if E2 could inhibit it in VSMC. Methods and Results-We show that in VSMC, E2 inhibits the RhoA-Rock pathway in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 53 publications
2
36
0
Order By: Relevance
“…Importantly, AMPK is able to phosphorylate RhoA on Ser188 and to restrain its activity 41. Therefore, we speculated that RhoA mediated the effect of miR-23a-ATG12 axis on melanoma invasion and migration downstream of AMPK.…”
Section: Resultsmentioning
confidence: 98%
“…Importantly, AMPK is able to phosphorylate RhoA on Ser188 and to restrain its activity 41. Therefore, we speculated that RhoA mediated the effect of miR-23a-ATG12 axis on melanoma invasion and migration downstream of AMPK.…”
Section: Resultsmentioning
confidence: 98%
“…Phenotypic features of AMPKα1 deficient mice include accelerated erythrocyte death [35,36,37], increased bone remodelling and reduced bone mass [38,39,40], increased skeletal muscle mass [41,42,43], altered endothelial and vascular functions [44,45,46,47,48], altered epithelial transport [49,50], decreased insulin release [51], enhanced susceptibility to insulin resistance and obesity [52], asthenozoospermia [53] as well as altered circadian rhythm [54]. Despite altered function of AMPKα1 deficient dendritic cells [32], AMPKα1 deficient mice had no striking defects in immunocompetence and displayed normal cell proliferation, humoral, cytotoxic and delayed-type hypersensitivity (DTH) responses following antigen injection [55].…”
Section: Introductionmentioning
confidence: 99%
“…While the exact mechanism of AMPK-mediated, VASP-dependent inhibition of cell cycle progression remains unclear, it has been suggested that VASP is necessary for Rho-dependent, serum response element (Sre)-mediated transcriptional activity [29,34]. Additionally, it has been suggested that AMPK exhibits inhibitory crosstalk with RhoA in ASM cells [35]. Given this insight and the new evidence presented here that AMPK exerts regulatory impact on VASP, we can speculate that AMPK inhibits ASM cell proliferation via inhibitory regulation of VASP, possibly through VASP-dependent Sre transcriptional activity; however, further investigation into these exact mechanisms are needed.…”
Section: Discussionmentioning
confidence: 99%